1991
DOI: 10.1002/1520-6750(199104)38:2<183::aid-nav3220380206>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of stochastic activity networks using path control variates

Abstract: This article details several procedures for using path control variates to improve the accuracy of simulation‐based point and confidence‐interval estimators of the mean completion time of a stochastic activity network (SAN). Because each path control variate is the duration of the corresponding directed path in the network from the source to the sink, the vector of selected path controls has both a known mean and a known covariance matrix. This information is incorporated into estimation procedures for both no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…In previous experimentation [4], we found that the assumption of joint normality (11) between the response and the controls becomes increasingly untenable as the relative dominance increases; and this results in serious degradation in confidenceinterval coverage. To assess the effect on confidence-interval coverage of departures from the normality assumption, we set the relative dominance at three broad levels (low, medium, and high); and to assess the effect of sample size n, we performed simulation experiments involving n = 48, 96, and 192 independent replications.…”
Section: Experimental Evaluationmentioning
confidence: 93%
See 1 more Smart Citation
“…In previous experimentation [4], we found that the assumption of joint normality (11) between the response and the controls becomes increasingly untenable as the relative dominance increases; and this results in serious degradation in confidenceinterval coverage. To assess the effect on confidence-interval coverage of departures from the normality assumption, we set the relative dominance at three broad levels (low, medium, and high); and to assess the effect of sample size n, we performed simulation experiments involving n = 48, 96, and 192 independent replications.…”
Section: Experimental Evaluationmentioning
confidence: 93%
“…For each nondummy activity duration V i in a given network, the associated distribution was taken to be either (a) a normal distribution with a specified mean µ i and standard deviation σ i = µ i /4 whose tail was truncated below the value 0; or (b) an exponential distribution with a specified mean µ i . We chose the exponential distribution as the nonnormal alternative for reasons elaborated in [4]. For network 1 the set of activities with durations as in (a) was taken to be {(1,3), (2,6), (2,4), (8,11), (10,13), (12,18), (16,17) The following rule was used for selecting control variates.…”
Section: Experimental Evaluationmentioning
confidence: 99%
“…We use numerical experiments to evaluate the actual performance of the convex approximation, defined in (35), of the stochastic activity network investment problem. We consider a single stochastic activity network given in Elmaghraby (1977) and also used in Avramdidis et al (1991). Figure 3 depicts the precedence relations between the activities.…”
Section: Computational Studymentioning
confidence: 99%
“…We assume that all random variables, ω i , are independently distributed and follow a truncated normal distribution. The mean, µ i , is the same as in Elmaghraby (1977) and Avramdidis et al (1991) and differs per activity i, whereas the standard deviation σ is the same for each arc, but varies over the experiments. Furthermore, we also vary the budget B and the upper bound, b, on the investments; the per unit investment costs are c i = 1 for every activity and every experiment.…”
Section: Computational Studymentioning
confidence: 99%
“…To form a control-variate estimator, we use the same approach as in Avramidis, Bauer, and Wilson (1991). Ranking the directed r-s paths in decreasing order of expected duration, we let t l , t~, & be the first three such paths.…”
Section: Conditional Expectation and Control Variatesmentioning
confidence: 99%